Self-Esteem and Sense of Purpose in Adolescents from Economically Disadvantaged Families - Reba, Yansen Alberth; Muttaqin, M. Zaenul (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Being a teenager from a low-income home typically has a detrimental effect on many aspects of life. Teens under these circumstances confront a variety of difficulties that call for emotional fortitude and a distinct sense of direction. It is frequently necessary for these teenagers to develop self-worth and have purpose in their lives, even in the face of financial difficulties. The purpose of this study is to investigate the connection between teenagers from low-income households in Kota Jayapura's feeling of purpose and self-worth. Utilising a Spearman rho correlation design, a quantitative research methodology is applied. Using a purposive sample approach, 150 teenagers from economically disadvantaged homes, ages 16 to 19, were chosen to participate. The Purpose in Life Questionnaire (α = 0.920) and the Self-Esteem Scale (α = 0.890) were used in the study. The findings showed that self-esteem and sense of purpose had a strong positive link (r = 0.320, p < 0.001), with self-esteem in these teenagers accounting for 10.3% of the sense of purpose. Teens who are struggling financially must build their self-esteem to feel more purposeful in life. It is anticipated that future research will create intervention plans specifically suited for teenagers from low-income homes in order to promote their general well-being and personal growth.